Readiness of Early Childhood Education (ECE) Teachers in West Java for 21st Century Learning: A Survey Study - Rahmi, Yosita Nadila; Putri, Suci Utami; Dewi, Finita (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2024)
This study explores the readiness of Early Childhood Education (ECE) teachers in West Java for 21st-century learning. Utilising a survey research design, an online questionnaire was distributed via WhatsApp to ECE teachers across multiple regions in West Java. The survey assessed teacher readiness based on Jan's (2017) characteristics of 21st-century educators, covering aspects such as student-centred classrooms, personalised instruction, technology competence, social competence, and continuous learning. Responses from 186 teachers were analysed using a Likert scale approach, revealing high readiness in learning management and social competence but moderate readiness in technology-related competencies. The findings indicate that while teachers are well-prepared to manage student-centred learning environments, there is a need for improved ICT training, particularly in areas like using digital tools and social media for educational purposes. Additionally, while social competence is strong, continuous professional development in technology integration remains essential. The study highlights the necessity of targeted professional development programs to bridge these gaps and ensure teachers are equipped with the skills needed for 21st-century education. These implications highlight the need for comprehensive teacher training programs and supportive professional communities to ensure ECE teachers can effectively meet the demands of modern education. Despite the study's geographical limitation to West Java and reliance on self-reported data, it provides valuable insights into the preparedness of ECE teachers. It suggests directions for future research to expand understanding across diverse contexts.